Normative Juridical Review of Corporate Zakat Obligations as Legal Subjects in the National Zakat Legal System - Ramadhan, Ardiansyah; Akhmad Farroh Hasan (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2025)
Previous studies on corporate zakat have primarily focused on the different fiqh perspectives regarding whether a company can be classified as a muzakki (zakat payer) and how this relates to Indonesia's zakat regulations. These studies generally divide scholarly opinions into two camps: one that rejects corporate zakat due to the absence of explicit texts in hadith and the view that zakat is only obligatory for individual,mukallaf Muslims; and another that accepts the company as a shakhṣiyyah iʿtibāriyyah (legal entity) equivalent to a juridical person obligated to pay zakat. Although both perspectives reference Article 1 point 5 of Law No. 23 of 2011 on Zakat Management, their analysis remains descriptive and limited to comparative opinions. A systematic juridical reading of the company's legal status as a zakat subject within the national zakat system is still lacking. This article addresses that gap by applying a normative legal approach to explore the company's position as a legal subject under Islamic law and national legislation. It emphasizes the need for legal reform to explicitly integrate corporate zakat into Indonesia's zakat regulatory framework. The novelty lies in its systematic normative approach to establishing corporate zakat as a juridical obligation, contributing to the development of Islamic law and zakat governance in the modern state context.